2022
DOI: 10.1021/acssuschemeng.2c05058
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Analysis of a Highly Efficient CO2 Separation Process Using Flexible Metal–Organic Frameworks with Isotherm Hysteresis

Abstract: To realize large-scale CO 2 separation to prevent global warming, energy and space saving separation technologies are required. Flexible metal−organic frameworks (flexible MOFs) with gate-opening properties have been found to be promising adsorbents, but the unconventional sigmoidal shapes and hysteresis of the isotherms have hindered quantitative evaluation of their applications in separation processes. This paper is the first to evaluate ELM-11, a flexible MOF that exhibits sigmoidal isotherms with hysteresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 49 publications
(78 reference statements)
2
20
0
Order By: Relevance
“…Assumption 5 can be supported by Kondo et al [35] which reported that the double exponential model is in good agreement with the time profile data of adsorption volume for ELM-11. Assumption 6 is considered reasonable based on the results of Yang et al [14] and Takakura et al, [36] where nitrogen adsorption on ELM-11 has been confirmed to be negligible We verified their study by measuring the N 2 adsorption isotherms of ELM-11 in the pressure range of 0-20 bar at temperatures of 273 and 298 K, which show that adsorption of N 2 on ELM-11 is negligible. Assumption 8 can be found in Casas et al, [37] where only the delay due to the internal pipe volume is considered.…”
Section: Modeling Of Breakthrough Tests (Experiments 2)supporting
confidence: 64%
See 1 more Smart Citation
“…Assumption 5 can be supported by Kondo et al [35] which reported that the double exponential model is in good agreement with the time profile data of adsorption volume for ELM-11. Assumption 6 is considered reasonable based on the results of Yang et al [14] and Takakura et al, [36] where nitrogen adsorption on ELM-11 has been confirmed to be negligible We verified their study by measuring the N 2 adsorption isotherms of ELM-11 in the pressure range of 0-20 bar at temperatures of 273 and 298 K, which show that adsorption of N 2 on ELM-11 is negligible. Assumption 8 can be found in Casas et al, [37] where only the delay due to the internal pipe volume is considered.…”
Section: Modeling Of Breakthrough Tests (Experiments 2)supporting
confidence: 64%
“…A model for sigmoidal isotherms has been proposed by Hefti et al [20] in the form of a weighted dual-site Langmuir equation, which was employed for ELM-11 in our recent study. [36] In this model, the adsorption isotherm of ELM-11 is modeled by a weighted sum of the two isotherm equations for two different mechanisms: an isotherm n L , which occurs only when the gate is closed, and the other adsorption isotherm n U , which occurs only when the gate is open:…”
Section: Modeling Of Adsorption Isotherms (Experiments 1 and 2)mentioning
confidence: 99%
“…As for other adsorbents with stepped isotherms, the step pressure increases to a higher pressure with temperature. 6,7,9,20,22 Like MIL-53(Al), 36 a prototypical “phase-change” adsorbent, N 2 does not show a stepped isotherm under the same measurement conditions as CO 2 . However, a key difference to MIL-53(Al) is that when the step occurs, F4_MIL-140A(Ce) does not show any hysteresis during desorption (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…60,[62][63][64] Our process model does not currently have the ability to consider desorption hysteresis and hysteresis loop scanning, which explains why we did not include MIL-53(Al) in this comparison. However, given the recent work by Takakura et al, 20 this could present an opportunity for future work. Another factor is that the step in the CO 2 isotherm of MIL-53(Al) does not occur until very high CO 2 partial pressures at the temperatures considered in this work (6-8 bar a at 298 K), 7 which would not be achieved even under the PSA conditions investigated here.…”
Section: Process Modellingmentioning
confidence: 98%
See 1 more Smart Citation